The impact of a telemedicine intervention on home non‐invasive ventilation in a rural population with advanced COPD. (18th March 2021) - Leonard, Rachel; Forte, Michael; Mehta, Devanshi; Mujahid, Hassan; Stansbury, Robert
Abstract: Introduction: Rural regions have unique challenges with the implementation of new therapies upon discharge from the hospital due to multiple barriers. Objectives: We investigated the effect of home non‐invasive ventilation (NIV) plus the implementation of a call center following hospitalization for acute exacerbations of COPD (chronic obstructive lung disease) on NIV usage and readmissions. Methods: In this prospective pilot study, consecutive patients were screened at our institution for diagnosis of hypercarbic respiratory failure or COPD exacerbation from 2018 to 2019. Patients with more than two admissions in the last year were reviewed for eligibility. Of the 82 patients screened, 22 were eligible. There were 10 participants randomized to the intervention (NIV and call center) arm and 10 to NIV alone. Results: A total of 20 patients were randomized (mean age of 64, 45% males, BMI of 32). At three months, average usage was 32.1 days out of 90, 35%. When comparing the call center group to the standard group, there was a statistically significant difference in total days of device usage 48.7 compared to 15.5 (significant U‐value of 16, critical value of U at p<.05 of 27) and cumulative use in hours 284 versus 87.7 (significant U ‐value of 20). Participants in the call center group were readmitted on average 4.2 times compared to 2.4 in the control group which was not statistically different (non‐significant U ‐value of 42). In the follow‐up period, 9/20 (45%) of the participants died. Conclusion: This pilot study highlights the challenges in implementing care for advanced COPD in a rural population. Our data suggest that telemedicine may favorably address therapy adherence.